Reimagining service learning in the AI Era: Novice teachers’ perceptions of life and career skills and community participation - Shahpo, Samia Mokhtar; Almadani, Nora A; Alfadil, Noha Hsan; Alomair, Maryam Ahmed; Hamid, Alaaeldin Ahmed; Yaseen, Mahmoud Mohamed (Research Journal in Advanced Humanities, 2026)
This study explores how novice teachers make sense of life and career skills, community participation, and the role of artificial intelligence within service learning in the AI era. It adopts a mixed-methods sequential explanatory design, drawing on data from 362 novice teachers across Saudi Arabia, Egypt, and Sudan. A structured questionnaire was used to examine three key dimensions: perceptions of life and career skills, perceptions of community participation, and perceptions of artificial intelligence in service learning contexts, followed by semi-structured interviews with a randomly selected group of participants to gain deeper insights. The findings suggest that novice teachers place strong value on life and career skills, especially problem-solving, critical thinking, and communication, which they see as essential for dealing with everyday classroom challenges. However, some areas, such as leadership and time management, appear less consistently developed, reflecting the realities of early career teaching. Community participation is also viewed positively, yet actual engagement remains limited, with teachers pointing to workload, time constraints, and limited institutional support as key barriers. In relation to artificial intelligence, teachers generally express positive attitudes, particularly regarding its role in supporting teaching practices, improving access to resources, and encouraging creativity. However, uncertainty remains about how to meaningfully integrate AI into service learning and community engagement. Overall, the study highlights a transitional stage in teaching, where professional skills, community engagement, and technology are present but not yet fully integrated, pointing to the need for more connected and practice-oriented approaches in teacher development.